First-principles study of the structure of water layers on flat and stepped Pb electrodes - Lin, Xiaohang; Evers, Ferdinand; Groß, Axel (Beilstein Journal of Nanotechnology, 2016)
On the basis of perodic density functional theory (DFT) calculations, we have addressed the geometric structures and electronic properties of water layers on flat and stepped Pb surfaces. In contrast to late d-band metals, on Pb(111) the energy minimum structure does not correspond to an ice-like hexagonal arrangement at a coverage of 2/3, but rather to a distorted structure at a coverage of 1 due to the larger lattice constant of Pb. At stepped Pb surfaces, the water layers are pinned at the step edge and form a complex network consisting of rectangles, pentagons and hexagons. The thermal stability of the water layers has been studied by using ab initio molecular dynamics simulations (AIMD) at a temperature of 140 K. Whereas the water layer on Pb(111) is already unstable at this temperature, the water layers on Pb(100), Pb(311), Pb(511) and Pb(711) exhibit a higher stability because of stronger water–water interactions. The vibrational spectra of the water layers at the stepped surfaces show a characteristic splitting into three modes in the O–H stretch region.
Keywords: density functional theory calculations; Pb surfaces; stepped surfaces; vibrational spectrum; water structure